Enhancing the teaching of structural dynamics using additive manufacturing. (1st December 2017) - Virgin, Lawrence
Highlights: A practical, educational augmentation for teaching structural dynamics. Innovative use of 3D printing. Measurement of natural frequencies. Justification for sway approximations. Parameter variations and how geometry influences vibration. Abstract: This paper provides a companion study to a previous paper by the same author (Virgin, 2017). In that paper, 3D printing was used to provide a hands-on experience for students of (linear) structural analysis based on the lateral stiffness of plane frames. In this paper, a related set of structural plane frames is investigated in terms of their natural frequencies, perhaps the fundamental feature in structural dynamics. Again, a 3D printer is used to provide a variety of parameter variations, and the extent to which certain simplifying analytical assumptions are justified is assessed.